2018
DOI: 10.1021/acsomega.7b01886
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Reactive Anchoring Lipids with Different Performance for Cell Surface Re-engineering Application

Abstract: Introduction of selectively chemical reactive groups at the cell surface enables site-specific cell surface labeling and modification opportunity, thus facilitating the capability to study the cell surface molecular structure and function and the molecular mechanism it underlies. Further, it offers the opportunity to change or improve a cell’s functionality for interest of choice. In this study, two chemical reactive anchor lipids, phosphatidylethanolamine–poly(ethylene glycol)–dibenzocyclooctyne (DSPE–PEG2000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Various techniques have been developed to modify or engineer cell surface and liposomes. For examples, chemical reactive anchor lipids, phosphatidylethanolamine-poly-(ethylene glycol)dibenzocyclooctyne and cholesterol-PEG-dibenzocyclooctyne, have been synthesized to study the structure, function and molecular mechanism of cell surface molecules [48] . Cell lipid membrane has been modified with poly(ethylene glycol)-conjugated phospholipids with uniform distribution [49] .…”
Section: Advanced Surface Tagging Technologymentioning
confidence: 99%
“…Various techniques have been developed to modify or engineer cell surface and liposomes. For examples, chemical reactive anchor lipids, phosphatidylethanolamine-poly-(ethylene glycol)dibenzocyclooctyne and cholesterol-PEG-dibenzocyclooctyne, have been synthesized to study the structure, function and molecular mechanism of cell surface molecules [48] . Cell lipid membrane has been modified with poly(ethylene glycol)-conjugated phospholipids with uniform distribution [49] .…”
Section: Advanced Surface Tagging Technologymentioning
confidence: 99%
“…Specifically, cholesterol was used for its ability to intercalate into lipid rafts (Karp & Zhao, 2014; Simons & Ikonen, 2000). Sun et al showed cholesterol‐PEG can be used to modify 99% of cells in a population (Vabbilisetty, Boron, Nie, Ozhegov, & Sun, 2018). As a result, we hypothesized that lipid insertion would allow for modification of a higher fraction of cells than covalent methods.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are three categories of modification strategies: (1) hydrophobic interaction, (2) covalent conjugation, and (3) electrostatic interaction. Lipid-PEG has attracted much attention for its ability to form a uniform ultrathin coating on the surface of cells without covalent bonds or electrostatic interactions, either one of which can lead to severe cytotoxicity [14].…”
Section: Introductionmentioning
confidence: 99%